Use of eDNA to Determine Source Locations of Deadly Jellyfish (Cubozoa) in an Open Coastal System - Scott J. Morrissey; Dean R. Jerry; Michael J. Kingsford (Coasts, 2024)
Challenges associated with cubozoan jellyfish detection and the limitations of current detection techniques limit the ability of scientists to fill critical knowledge gaps surrounding their ecology. Environmental DNA (eDNA), however, has proven useful as an ecological survey tool to detect and study these deadly jellyfish. This study aimed to leverage the power of eDNA to detect and explore the distribution of the Australian box jellyfish (Chironex fleckeri), encompassing both its medusae and polyp life history stages, within an open coastal bay (Horseshoe Bay) of Magnetic Island, Queensland, Australia. Our investigation focused on a hypothesis concerning the source locations of the jellyfish within Horseshoe Bay and, through a comparison of both life history stage distributions, aimed to determine potential population stock boundaries. eDNA results aligned with the predicted nearshore distribution of medusae. Further, the elusive benthic polyp stage was also detected. These findings confirmed Horseshoe Bay as a source location of the jellyfish. Moreover, our evidence supported a model that the area likely represents a population stock of the species. This adds to growing evidence suggesting some cubozoan jellyfish have population stocks of small spatial scales in both open and relatively closed ecosystems such as estuaries. In conclusion, this study serves as a notable example of eDNA’s ability to resolve critical knowledge gaps surrounding cubozoan ecology and to enhance the management ability of these deadly jellyfish to reduce envenomations.